A challenging case of prolactinoma in pregnancy - Sinha, Sweta; Bhorania, Riddhi; Shah, Dipal; Sapre, Shilpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Prolactinomas are the most common functional tumour of pituitary gland arising from lactotrophs. Microadenomas constitute 90% and the rest are macroadenomas. Females are more prone to develop macroadenomas. High estrogen levels during pregnancy leads to increase in the size of prolactinomas thereby leading to compression of optic chiasma. This eventually manifests as visual symptoms and headache. Pharmacotherapy with dopamine agonists is the treatment of choice. We present here a case of prolactinoma in a pregnant woman whose symptoms worsened due to increase in size of the tumor. Multidisciplinary management resulted in successful outcome.